2021
DOI: 10.51791/njap.v48i2.2924
|View full text |Cite
|
Sign up to set email alerts
|

© Effect of strain and sex on haematological and serum biochemical indices of tropical indigenous chickens

Abstract: A thirteen-week experiment was conducted to determine the effect of sex and strain on the  haematological and serum biochemical indices of two indigenous chicken strains (FUNAAB  Alpha and Yoruba ecotype) in the African subtropics. One hundred and twenty chickens  comprising thirty (30) each of FUNAAB Alpha males, FUNAAB Alpha females, Yoruba  ecotype males and Yoruba ecotype females were assigned to four treatments consisting of  three replicates of ten (10) chickens each, in a 2 x 2 factorial arrangement of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
1
2
0
3
Order By: Relevance
“…Blood cholesterol levels were similar (P > 0.05) among birds fed the dietary treatments. The serum cholesterol values are however within the reference values 129-297 mg/dl reported by Adewole et al [54].…”
Section: The Results Of Tablesupporting
confidence: 82%
“…Blood cholesterol levels were similar (P > 0.05) among birds fed the dietary treatments. The serum cholesterol values are however within the reference values 129-297 mg/dl reported by Adewole et al [54].…”
Section: The Results Of Tablesupporting
confidence: 82%
“…Sex had no significant influence (p>0.05) on all the haematological parameters except for WBC where females had the higher values. The findings of Adewole et al 23 , reported that sex had no significant influence on all haematological parameters except for red blood cell count that was significantly affected in broiler where the male had higher values. This result is consistent with those of Schmidt et al 24 , who reported that sex did not affect RBC, WBC and Hb.…”
Section: Discussionmentioning
confidence: 91%
“…This study showed relatively normal glucose levels. Normal glucose levels in the blood of laying hens are around 197-299 mg/dl (Adewole et al, 2021). Glucose levels with probiotic treatment showed a tendency to decrease compared to control.…”
Section: Glucose Levelsmentioning
confidence: 95%